2009
DOI: 10.1007/s12010-009-8655-3
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Paeonol and Emodin by Transgenic Crown Galls of Panax quinquefolium

Abstract: Two aromatic substrates, paeonol (1) and emodin (2), were biotransformed by using transgenic crown galls of Panax quinquefolium. Four biotransformed products (3-6) were isolated and identified by physicochemical and spectral methods. A beta-glucoside (3, 73.2% of biotransformation yield) and a 1-(2,4-dimethoxyphenyl)- ethanone (4, 8.03%) were isolated from the suspension cultures after 7-day incubation of substrate 1. Upon administration of substrate 2, another beta-glucoside [emodin-6-O-beta-D: -glucopyranosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…For example, in the biotransformation system of crown galls of P. quinquefolium: paeonol was monoglucosylated to yield paeonol-2-O-β-D-glucopyranoside [20]. While, in our research, it's the first time to biotransform chalcone using the transgenic crown galls of P. quinquefolium.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, in the biotransformation system of crown galls of P. quinquefolium: paeonol was monoglucosylated to yield paeonol-2-O-β-D-glucopyranoside [20]. While, in our research, it's the first time to biotransform chalcone using the transgenic crown galls of P. quinquefolium.…”
Section: Discussionmentioning
confidence: 68%
“…Usually, the system of transgenic crown galls of panax quinquefolium was reported to use for the glycosylation of substrate, including the biotransformation of phenolic acids [19], anthraquinone [20], sesquiterpenes [21]. For example, in the biotransformation system of crown galls of P. quinquefolium: paeonol was monoglucosylated to yield paeonol-2-O-β-D-glucopyranoside [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work (Ma et al 2009), paeonol and emodin were used as substrates to investigate the biotransformation ability of crown galls of P. quinquefolium, and three reaction types occurred: glycosylation, hydroxylation and methylation. In this present study, further confirmation was obtained about the reaction types of glycosylation and methylation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] Compared with callus and cell culture, the crown gall cultures grow faster, produce more active constituents, and are free of exogenous phytohormones. [ 11 15 16 ] The results of our previous studies demonstrated that the crown galls of P. quinquefolium had the capacities to catalyze glycosylation, hydroxylation and methylation reactions. [ 16 17 ] In order to explore new plant biotransformation system by feeding AA as precursor, and to find out novel artemisinin derivatives with good anti-malaria and/or antitumor activities, the biotransformation of AA by crown galls of P. quinquefolium was investigated in the present paper.…”
Section: Introductionmentioning
confidence: 99%